Sosialisasi Akad-Akad Transaksi Keuangan Syariah Pada Siswa Akuntansi SMK Satria Jakarta - Astuti, Retno Puji; Wahyuni, Putri Dwi; Marlina, Rini (Edumedia Solution, 2023)
There are many provisions that must be carried out for a Muslim in doing business. The provisions that have been stipulated in the Qur'an and hadith, which make Muslims obey the teachings of Islam, besides that the provisions also bring benefits to the benefit of human life. In practice, sharia transactions are free from elements of usury, gharar, and maysir. To avoid these things, a contract is made that underlies the transaction so that it is safer and does not harm both parties.Â The purpose of this community service activity is to increase the comprehensive and integrative understanding of students majoring in accounting at SMK Satria Jakarta regarding contracts in Islamic financial transactions. This activity is also in line with government programs to increase Sharia transactions which will contribute to the National economy.Â This activity is carried out by conducting socialization of Islamic financial transaction contracts through a virtual room in the zoom application. With this training, students gained additional knowledge about Islamic financial transaction contracts and the participants were satisfied with the material that was socialized.